Railway Discrimination - Dunn, Samuel O. (Journal of Political Economy, 1912)
The main purpose of the original Interstate Commerce act, and of the various measures that have been passed to amend it, has been the suppression of unfair railway discrimination. The most pernicious form such discrimination formerly took was that of secret rebating. It is popularly believed, because secret rebating has been almost extirpated, that the suppression of unfair discrimination has become secondary in importance to the prevention of excessive rates. This belief is, to a large extent, unfounded. Its prevalence makes needful emphasizing of the facts that unfair discrimination continues, that it still produces baneful results, and that its suppression and prevention still are, or ought to be, the main object of government regulation of railway traffic. I would not be misunderstood as saying or implying that the condition in respect to railway discrimination is as bad as in years past. On the contrary, there has been a very marked improvement since the Hepburn act went into effect in i906. There never was a time in the history of American railways when there was so little unfair discrimination as there is now. But existing conditions fall short of being what they ought to be. There still are many evil forms of discrimination; and what is worse, many of them under existing laws cannot be stopped or prevented by either the railways or the Interstate Commerce Commission. The railways cannot stop or prevent many of them, because to do so their managers would have to make arrangements which